Hyper crosslinked polymer supported NHC stabilized gold nanoparticles with excellent catalytic performance in flow processes. Issue 4 (29th November 2022) - Eisen, Constantin; Ge, Lingcong; Santini, Elena; Chin, Jia Min; Woodward, Robert T.; Reithofer, Michael R.
Abstract : Gold nanoparticles stabilized in a HCP·NHC network showing excellent catalytic activity in flow application. Abstract : Highly active and selective heterogeneous catalysis driven by metallic nanoparticles relies on a high degree of stabilization of such nanomaterials facilitated by strong surface ligands or deposition on solid supports. In order to tackle these challenges, N-heterocyclic carbene stabilized gold nanoparticles (NHC@AuNPs) emerged as promising heterogeneous catalysts. Despite the high degree of stabilization obtained by NHCs as surface ligands, NHC@AuNPs still need to be loaded on support structures to obtain easily recyclable and reliable heterogeneous catalysts. Therefore, the combination of properties obtained by NHCs and support structures as NHC bearing "functional supports" for the stabilization of AuNPs is desirable. Here, we report the synthesis of hyper-crosslinked polymers containing benzimidazolium as NHC precursors to stabilize AuNPs. Following the successful synthesis of hyper-crosslinked polymers (HCP), a two-step procedure was developed to obtain HCP·NHC@AuNPs. Detailed characterization not only revealed the successful NHC formation but also proved that the NHC functions as a stabilizer to the AuNPs in the porous polymer network. Finally, HCP·NHC@AuNPs were evaluated in the catalytic decomposition of 4-nitrophenol. In batch reactions, a conversion of greater than 99% could be achieved in as little as 90 s. To further evaluate the catalytic capability of HCP·NHC@AuNP, the catalytic decomposition of 4-nitrophenol was also performed in a flow setup. Here the catalyst not only showed excellent catalytic conversion but also exceptional recyclability while maintaining the catalytic performance.